2007
DOI: 10.1007/s10327-007-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Spongospora subterranea soil contamination and its relationship to severity of powdery scab on potatoes

Abstract: We investigated soil contamination by Spongospora subterranea f. sp. subterranea (Sss) and disease severity of powdery scab in 29 potato fields in Hokkaido, Japan, using a hydroponic culture method with tomato seedlings as bait plants. The quantity of Sss infection on the roots of bait plants was evaluated using the polymerase chain reaction (PCR) and expressed in terms of the infection potential in the soil. The infection potential was positively correlated with the disease severity of harvested tubers, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Soil samples taken at planting and harvest time at the same positions in a field and tested with ELISA gave an increasingly positive result during the season. Even at positions where the ELISA tests gave negative or slightly positive results, tuber infection levels were often high, and these results are similar to those of Nakayama et al (2007). Variation of the ELISA data derived from 96 soil samples evenly distributed over the field (0.5 ha; grid mesh size 10 m × 5 m) confirmed other reports that soil contamination is unevenly distributed.…”
Section: Soil Inoculum and Disease Risksupporting
confidence: 85%
See 3 more Smart Citations
“…Soil samples taken at planting and harvest time at the same positions in a field and tested with ELISA gave an increasingly positive result during the season. Even at positions where the ELISA tests gave negative or slightly positive results, tuber infection levels were often high, and these results are similar to those of Nakayama et al (2007). Variation of the ELISA data derived from 96 soil samples evenly distributed over the field (0.5 ha; grid mesh size 10 m × 5 m) confirmed other reports that soil contamination is unevenly distributed.…”
Section: Soil Inoculum and Disease Risksupporting
confidence: 85%
“…They estimated > 10,000 sporosori/g in the soil where the highest disease incidence was found. In contrast to this high number, the estimated sporosorus density of the four fields with the highest crop disease incidence tested by Nakayama et al (2007) varied from 0.1 to 105 per gram of soil. Merz (1993) compared root infection in a bioassay, baiting a series of inoculated soils together with naturally infested field soils, and concluded that a highly infested field soil contains > 500 sporosori/g.…”
Section: Soil Inoculum and Disease Riskmentioning
confidence: 78%
See 2 more Smart Citations
“…Hereafter, the DNA extraction procedure was performed basically as described by Nakayama et al (Nakayama et al 2007a), and the pellet obtained was dissolved in 200 µl TE (10 mM Tris, 1.0 mM ethylenediaminetetraacetic acid [EDTA], pH 8.0). The PCR reaction mixture (20 µl) was prepared by adding 1.6 µl of 2.5 mM dNTPs (Takara Bio Inc., Otsu, Japan), 0.5 µl of 20 µM forward (Sps1; 5′-CCTGGGTGCGATTGTCTGTT-3′) and 0.5 µl of 20 µM reverse (Sps2; 5′-CACGCCAA TGGTTAGAGACG-3′) primers (Bell et al 1999), 2 µl of 10× PCR buffer (Takara Bio Inc.), 0.1 µl of Taq polymerase (TaKaRa Taq, 5 U µl −1 , Takara Bio Inc.) and 4 µl of the template DNA solution to 11.3 µl of sterile distilled water.…”
Section: Detection Of Spongospora Subterranea From Bait Plantsmentioning
confidence: 99%